2006
DOI: 10.1007/s10529-006-9122-7
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Bypass Identified as Source of Chiral Contamination in l(+) and d(−)-lactate Fermentations by Recombinant Escherichia coli

Abstract: Two new strains of Escherichia coli B were engineered for the production of lactate with no detectable chiral impurity. All chiral impurities were eliminated by deleting the synthase gene (msgA) that converts dihydroxyacetone-phosphate to methylglyoxal, a precursor for both L: (+)- and D: (-)-lactate. Strain TG113 contains only native genes and produced optically pure D: (-)-lactate. Strain TG108 contains the ldhL gene from Pediococcus acidilactici and produced only L: (+)-lactate. In mineral salts medium cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 30 publications
1
94
1
Order By: Relevance
“…1B). The bacterial population was maintained at the exponential or early stationary phase in a fermentation vessel by serially transferring cultures into new media as previously described (20,21). In all three evolutionary trajectories, a rapid adaptation occurred that simultaneously increased xylose catabolism, lactate titer, and cell growth (Fig.…”
Section: Identification Of Primary Genetic Changes Of E Coli Adaptatmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). The bacterial population was maintained at the exponential or early stationary phase in a fermentation vessel by serially transferring cultures into new media as previously described (20,21). In all three evolutionary trajectories, a rapid adaptation occurred that simultaneously increased xylose catabolism, lactate titer, and cell growth (Fig.…”
Section: Identification Of Primary Genetic Changes Of E Coli Adaptatmentioning
confidence: 99%
“…To further demonstrate the application of our discovery in converting sugar mixtures into renewable chemicals, we substituted wildtype xylR with xylR (R121C and P363S) of a previously engineered D-lactate E. coli producer TG114, which efficiently converts glucose into D-lactate (21). Fermenting TG114 in a glucose-xylose mixture, 50 g·L −1 of each sugar, showed that only 34% of the xylose was used due to CCR (Fig.…”
Section: Characterization Of Physiological Effects Of Convergent Mutamentioning
confidence: 99%
“…This is more critical as we attempt to replace petroleum-based plastics with renewable PLA-based plastics, which would require production of the base chemical in large quantities and lignocellulosic biomass as the feedstock for fermentation. Biocatalysts currently being developed to reduce the cost of production of optically pure isomers of lactic acid include Kluyveromyces (Bianchi et al, 2001;Porro et al, 1999), Saccharomyces (van Maris et al, 2004;Saitoh et al, 2005), Pichia (Ilmen et al, 2007), Rhizopus (Skory, 2000) and Lactobacillus (Liu et al, 2007); however, Escherichia coli stands out as an excellent microbial biocatalyst for this purpose (Dien et al, 2001;Grabar et al, 2006). E. coli is a well studied bacterium that uses glycolysis via the Embden-Meyerhoff-Parnas (EMP) pathway to convert hexose sugars into a mixture of acids (lactic, acetic, formic and succinic) and ethanol (Clark, 1989).…”
Section: Lactococcus Lactis and Lactococcus Casei As Well Asmentioning
confidence: 99%
“…Zhou et al (2003b) further engineered E. coli by deleting the native d-ldh gene and replacing it with the gene encoding L-(+)-LDH from Pediococcus to produce optically pure L-(+)-lactic acid. Further metabolic engineering and directed evolution led to E. coli strains, TG114 and TG108, that produced optically pure (99.9%) D-()) and L-(+)-lactate, respectively, from 12% w/v glucose at greater than 95% of the theoretical yield (Grabar et al, 2006). The very high lactic acid production titre and yield achieved by engineered E. coli strains TG114 and TG108 in simple salts medium is equal to or higher than the best values reported for lactic acid bacteria in complex medium (Table 2).…”
Section: Lactococcus Lactis and Lactococcus Casei As Well Asmentioning
confidence: 99%
See 1 more Smart Citation